An overview of the technological development on biofuels - Biodiesel and Ethanol - of Bric (Brazil, Russia, India and China), through the analysis of patent filings in the area - Costa, Eduardo Scopel Ferreira da (2012)
Orientador: Prof. Dr. Carlos Ricardo Soccol